2010
DOI: 10.1177/0143831x10377809
|View full text |Cite
|
Sign up to set email alerts
|

Management training as a source of perceived competitive advantage: The Mondragon Cooperative Group case

Abstract: The academic literature argues that managers, with their resources and capabilities, constitute a source of competitive advantage for companies, but that cooperatives generally have difficulties attracting and retaining competent managers. The present study examines the special efforts made in the creation and development of cooperative managers via corporate training centres in the Mondragon Cooperative Group. The fieldwork that supports this research is a qualitative study based on a series of in-depth inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 45 publications
1
47
0
8
Order By: Relevance
“…In Eroski, the research drew upon extensive knowledge of the Mondragon enterprises as they had been researched by the local team over many years (Albizu and Basterretxea, 1998;Basterretxea and Albizu, 2010, 2011a, 2011bBasterretxea, 2011;Basterretxea and Martínez, 2012). Additionally, for this specific comparative project of these two retailers, a common framework was developed and a common set of interview topics explored.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Eroski, the research drew upon extensive knowledge of the Mondragon enterprises as they had been researched by the local team over many years (Albizu and Basterretxea, 1998;Basterretxea and Albizu, 2010, 2011a, 2011bBasterretxea, 2011;Basterretxea and Martínez, 2012). Additionally, for this specific comparative project of these two retailers, a common framework was developed and a common set of interview topics explored.…”
Section: Methodsmentioning
confidence: 99%
“…They are expected to submit to continuous and critical internal scrutiny and control by cooperative members. This, together with controlled differential salaries between workers and managers, may make recruitment into the managerial cadre of worker cooperatives problematic (Eccles, 1981;Morales 2004;Basterretxea and Albizu, 2011a). It has also been suggested that managers coming from investor-owned firms find it difficult to adapt to the culture and values of the cooperatives.…”
Section: Literature On Employee-owned Businessesmentioning
confidence: 99%
“…En este sentido, la creación de la Escuela Politécnica fue solo la primera de las iniciativas que se llevaron a cabo en el campo educativo, otros centros educativos se han ido formando después hasta llegar en los años 90 a la fundación de un centro de investigación y docencia al máximo nivel: la Universidad de Mondragón. El protagonismo concedido a la formación en el Grupo también se considera un instrumento que favorece su competitividad (Basterretxea & Albizu, 2010) En relación al segundo aspecto, la participación, constituye otro componente esencial en el funcionamiento del Grupo. En Mondragón se intenta dar cabida siempre a todas las partes interesadas en el desarrollo de la experiencia, lo que se traduce en fórmulas de participación democrática para las personas socias, sean de trabajo o de otro tipo, en cada cooperativa (Mondragón Corporation, 2015).…”
Section: Educación Participación Y Transformación Social: Ejes Del Munclassified
“…Como hemos adelantado, se observa en esta estructura el ánimo de integrar en la cooperativa como socios a todos y cada uno de los agentes implicados en su desarrollo: productores del conocimiento y su gestión (profesorado y personal), consumidores del mismo (alumnado), y a los que se unen además socios interesados en la buena marcha de la iniciativa con la que se encuentran vinculados a través de la aportación de recursos económicos para ayudar al sostenimiento del proyecto, pero que también se verán después beneficiados por poder incorporar a personal directivo y gestor formado en estos centros universitarios. La formación de los líderes con que cuenta la organización en la Universidad se ha identificado como un instrumento que favorece la competitividad del grupo empresarial y que además ha solucionado la dificultad que implica buscar personal directivo para este tipo de organizaciones (Basterretxea & Albizu, 2010;Basterretxea & Albizu, 2011). …”
Section: La Participación En Mondragon Unibertsitateaunclassified
“…Essa teoria considera o desempenho superior como um fenômeno decorrente de características internas da empresa (VASCONCELOS; CYRINO, 2000). Dentro do debate, surgem pesquisadores que procuram identificar as principais fontes de vantagens competitivas, estejam elas dentro da empresa ou no ambiente externo (BARNEY, 1986;BASTERRETXEA;ALBIZU, 2011;BERMAN et al, 2002;SINGH, 1998;HATCH;DYER, 2004;IRELAND et al, 2002). Nas últimas décadas, parte desses pesquisadores começaram a reconhecer o conhecimento como uma fonte de vantagens competitivas para organizações sem fins lucrativos, empresas, governo e até mesmo países (DRUCKER, 2001;SENGE, 2002;HATCH;DYER, 2004).…”
Section: Introdução Ao Problema De Pesquisaunclassified